TARJIH PENAFSIRAN HURUF MUQATTHA’AH Al-QUR’AN PERSPEKTIF INTERTEKSTUALITAS - Said Agil Husin Al Munawar; Muhammad Hariyadi; Muhammad Ulyn Nuha (STIT AL-AMIN KREO TANGERANG, 2022)
The letter muqattha'ah has a râjih interpretation based on intertextuality in the munasabah verses of the Qur'an, hadith, asar, akwal tabiin, lughah, and ijtihad scholars. The name of the Prophet Muhammad is the meaning of râjih from Thâ Hâ and Yâ Sîn based on the letters muqattha'ah in the Qur'an using an intertextuality approach while still preserving the form of interpretation by being very careful to prioritize the intertextuality data that exists in each source, as well as some other meanings of râjih. The intertextuality perspective regarding muqattha'ah letters is found in 3 options, namely: Mandatory, Optional, and Unintentional, which indicates the potential for intertextuality and tarjih approaches in the interpretation of muqattha'ah letters. This journal has similarities with the opinion: 'Abdullâh bin 'Abbâs (w 68 H), and Qatâdah bin Du'âmah (w 118 H) that the letter means the name of the Prophet Muhammad. This journal differs from the opinion of Al-Sha'bî (w 103 H) and Al-Tsaurî (w 161 H) that the muqattha'ah letter cannot be interpreted, that it is the letter mu'jam only Allah knows its meaning. This journal uses the intertextuality method in interpreting the historical-critical-contextual interpretation of. While the approach used is a qualitative approach